2012
DOI: 10.1016/j.jvs.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed open conversions after endovascular abdominal aortic aneurysm repair

Abstract: Most OCs after EVAR are associated with significant morbidity and mortality, except when electively treating an isolated type II endoleak with ligation of branches and preservation of the endograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 20 publications
1
51
0
3
Order By: Relevance
“…This has been shown by some studies that have compared small subgroups of open conversion with and without graft salvage. 20 Several authors 16 have shown that graft salvage seems to be a valid option compared with graft removal, because in some comparative series, the mortality ranges from 1% to 4% when removing the graft and is 0 % when performing sacotomy with graft salvage. 20 This is, as far as we know, the largest case series of semiconversions in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown by some studies that have compared small subgroups of open conversion with and without graft salvage. 20 Several authors 16 have shown that graft salvage seems to be a valid option compared with graft removal, because in some comparative series, the mortality ranges from 1% to 4% when removing the graft and is 0 % when performing sacotomy with graft salvage. 20 This is, as far as we know, the largest case series of semiconversions in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several authors 16 have shown that graft salvage seems to be a valid option compared with graft removal, because in some comparative series, the mortality ranges from 1% to 4% when removing the graft and is 0 % when performing sacotomy with graft salvage. 20 This is, as far as we know, the largest case series of semiconversions in the literature. This technique, which was described first by Hinchliffe et al 14 in 2002, permits resolution of the endoleak in most cases by suturing the feeding vessel, and clamping of the aorta is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have documented the frequency of endovascular option use before open conversion. 6,7 We reviewed our institution's growing experience for late conversion of failed EVAR to better understand current results, predictors of outcome, and reasons for failure.…”
mentioning
confidence: 99%
“…It seems that the initial benefit of EVAR disappears in the intermediate and long term because of the need for frequent, meticulous, and costly follow-up and the potential need for reinterventions. Moreover, late open conversion after EVAR is reported to be associated with significant morbidity and mortality if explant of the stentgraft is inevitable, 12) and under this circumstance, suprarenal, and even supraceliac aortic clamping is often required. 13) Gupta and colleagues reported similar perioperative mortality after open surgery and EVAR in patients which made the aortic bifurcation 58 mm wide.…”
Section: Methodsmentioning
confidence: 99%